Comparing the Survival Outcomes of Radical Prostatectomy Versus Radiotherapy for Patients With De Novo Metastasis Prostate Cancer: A Population-Based Study - Guo, Xiaoxiao; Xia, Haoran; Su, Xiaonan; Hou, Huiming; Zhong, Qiuzi; Wang, Jianye (Frontiers in Oncology, 2021)
Purpose The efficacy of local treatments (LTs) in selected patients with metastatic prostate cancer (mPCa) had been demonstrated. However, the comparative effectiveness between LTs is unclear. Here, we compared the impact of radical prostatectomy (RP) and brachytherapy (RT) on the survival outcomes of mPCa patients. Materials and Methods mPCa patients who received RT or RP between 2004 and 2016 were identified from the Surveillance, Epidemiology, and End Results (SEER) database. Multivariable Cox proportional hazards analysis was used to evaluate the comparative risk of prostate cancer-specific mortality (CSM) and all-cause mortality (ACM) between LTs. A 1:1 propensity score matching (PSM) and adjusted standardized mortality ratio weighting (SMRW) were performed to balance the clinicopathological characteristics of the groups. Results Of 684 mPCa patients, 481 underwent RP and 203 received RT. After PSM, both groups included 148 cases, and RT resulted in comparable CSM versus RP [CSM: hazard ratio (HR) = 0.77, p = 0.325; ACM: HR = 0.73, p = 0.138], which was consistent with the SMRW model [CSM: HR = 0.83, p = 0.138; overall survival (OS): HR = 0.75, p = 0.132]. However, RP was associated with a lower CSM in the T1–2 subgroup (HR = 0.42, p = 0.048) and a lower ACM in the T1–2 (HR = 0.55, p = 0.031) and prostate-specific antigen (PSA) ≤20ng/ml (HR = 0.48, p = 0.022) subgroups. Besides, the results showed that the mortality risk was similar between the two groups in the T3–4, Gleason score (GS) >7, PSA >20 ng/ml, and all metastatic subgroups (all p > 0.100). Conclusions RP could confer better survival outcomes than could RT in mPCa patients with favorable primary tumor features, but not in those with advanced primary tumor features. Moreover, the metastatic substage has limited impact on the comparative effectiveness between RP and RT. Further clinical trials are necessary to confirm the present results.